1968
DOI: 10.1108/eum0000000005244
|View full text |Cite
|
Sign up to set email alerts
|

The first export order: a marketing innovation

Abstract: Surveys nine relatively new exporters with a view to defining their motivation and characteristics in relation to their first export orders. Suggests that the characteristics of these innovators/initiators of exporting are similar to those of innovators in other situations. Reveals that those who are likely to start exporting are those who have little loyalty to the UK marketing area. Underlines the importance of change agents in initiating the innovation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
92
0
2

Year Published

1988
1988
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 103 publications
(97 citation statements)
references
References 0 publications
3
92
0
2
Order By: Relevance
“…Firms' innovative culture, combined with appropriate accumulated knowledge stocks, engenders the development or improvement of products and new methods for doing business (Dosi, 1988;Nelson and Winter, 1982). Internationalization, or new entry into markets overseas, is an innovative act (Casson, 2000;Schumpeter, 1939;Simmonds and Smith, 1968), and born-global firms are particularly innovative in this regard.…”
Section: Conceptual Foundationsmentioning
confidence: 99%
“…Firms' innovative culture, combined with appropriate accumulated knowledge stocks, engenders the development or improvement of products and new methods for doing business (Dosi, 1988;Nelson and Winter, 1982). Internationalization, or new entry into markets overseas, is an innovative act (Casson, 2000;Schumpeter, 1939;Simmonds and Smith, 1968), and born-global firms are particularly innovative in this regard.…”
Section: Conceptual Foundationsmentioning
confidence: 99%
“…Simpson and Kujawa (1974) found that the perception of risk between entrepreneurs of companies that export and those that do not was signifi cantly different, but both groups indicated that the risk of exporting was greater than the risk of operating in domestic markets. Others have reported that entrepreneurs of exporting companies have a greater tendency to accept risk than their nonexporting counterparts (Dichtl et al, 1990;Simmonds & Smith, 1968). Leonidou et al (1998) found 10 studies investigating this issue, 8 of which found support for the positive association between degree of exports and risk tolerance.…”
Section: Perceptions Of the Environment (Risk Perception)mentioning
confidence: 94%
“…Such travels are likely to be associated with seeing specifi c foreign market opportunities as a means of overcoming the problems or limitations of domestic markets (Rao, 1977). Entrepreneurs whose fi rms are most active in exporting tend to have traveled most broadly (Simmonds & Smith, 1968). Leonidou et al identifi ed seventeen studies of the association of time spent abroad and degree of fi rm involvement with export markets.…”
Section: International Orientationmentioning
confidence: 99%
“…These factors were summarized by Fletcher (2001) into four categories: management characteristics; organizational characteristics; external impediments; and external incentives. By focusing on the first category, management characteristics, one finds, as cited in Fletcher (2001), that information about managers such as age [9], education [10], place of birth [11] can play an important role in the decision to internationalize. Relevant is also their foreign experience, such as time spent living abroad [12] and frequency of business trips [11], since these characteristics can influence the way managers comprehend the foreign market and understand their risks.…”
Section: International Career and Its Impact In On Firm' Internationamentioning
confidence: 99%
“…By focusing on the first category, management characteristics, one finds, as cited in Fletcher (2001), that information about managers such as age [9], education [10], place of birth [11] can play an important role in the decision to internationalize. Relevant is also their foreign experience, such as time spent living abroad [12] and frequency of business trips [11], since these characteristics can influence the way managers comprehend the foreign market and understand their risks. Studies that focused on startups and SMEs found a greater degree of importance in management's international experience for the internationalization success of such companies, due to the strong impact of the management team in a small company ( [13,14]; [15] as cited in [16]; [17]).…”
Section: International Career and Its Impact In On Firm' Internationamentioning
confidence: 99%